Integrated Silicon Photonics Remote Radio Frontend (RRF) for Single-Sideband (SSB) Millimeter-Wave Radio-Over-Fiber (ROF) Systems - Yeyu Tong; Chi-Wai Chow; Guan-Hong Chen; Ching-Wei Peng; Chien-Hung Yeh; Hon Ki Tsang (IEEE Photonics Journal)
Radio-over-fiber (ROF)-based mobile fronthaul network supporting the baseband unit and simple remote radio head is a promising network architecture for future wireless networks. In this paper, we propose and demonstrate a silicon photonics (SiPh)-based remote radio frontend (RRF) for the mm-wave ROF systems. The proposed SiPh-based RRF consisted of an integrated Mach–Zehnder modulator and a micro-ring modulator, producing a single-sideband 40 GHz millimeter-wave orthogonal-frequency-division-multiplexing ROF signal, which is robust against fiber chromatic dispersion in the mobile fronthaul transmission. The RRF is fabricated using SiPh platform and could be potentially low cost. High split-ratios can be potentially achieved. Data rate of 7.813 Gbit/s per wavelength channel is achieved in the experiment. Numerical analysis is also performed; there are good matches of the simulation and experimental results.